Efektivitas Penggunaan Website Live Worksheet pada Mata Pelajaran IPS Kelas IX di SMPN 4 Kota Solok - Syafwita, Hani (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2023)
This type of research is quantitative descriptive research. The population in this study were class IX social studies teachers and class IX students at SMP Negeri 4 Solok City, namely 3 teachers and 76 students. The sample in this study uses 2 research techniques, teachers use a technique (total sampling), while students use a technique (random sampling). The analysis technique in this research is descriptive quantitative using questionnaire criteria for effective and ineffective use of the live worksheet website. The research results show that: Live worksheets can help teachers create interesting learning evaluation questions, with a percentage of 83% being very effective in use. Meanwhile, live worksheets which can help students overcome boredom when taking exams with a percentage of 75% are effectively used. Based on the research results, it can be concluded that the use of the live worksheet website in social studies subjects in class IX at SMP Negeri 4 Solok City by teachers obtained a percentage of 83% which was very effective. Live worksheets that can help teachers create interesting learning evaluation questions. Meanwhile, based on the research results, it can be concluded that the use of the live worksheet website in class IX social studies subjects at SMP Negeri 4 Solok City by students obtained a percentage of 75% effective use.